2009
DOI: 10.1001/jama.2009.297
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Associated With Nosocomial Transmission of Oseltamivir- Resistant Influenza A(H1N1) Virus

Abstract: Context The sudden emergence and rapid spread of oseltamivir-resistant influenza A(H1N1) viruses with neuraminidase (NA) gene H274Y amino acid substitution is the hallmark of global seasonal influenza since January 2008. Viruses carrying this mutation are widely presumed to exhibit attenuated pathogenicity, compromised transmission, and reduced lethality. Objective To investigate nosocomial viral transmission in a cluster of patients with influenza A(H1N1) virus infection. Design, Setting, and Patients Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 10 publications
6
75
0
3
Order By: Relevance
“…Six patients developed pneumonia, and of these, 4 resulted in death from respiratory failure. [10][11][12] Preventing RV infection in HSCT recipients remains essential. The main preventive measures are influenza vaccination and avoiding contact with infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Six patients developed pneumonia, and of these, 4 resulted in death from respiratory failure. [10][11][12] Preventing RV infection in HSCT recipients remains essential. The main preventive measures are influenza vaccination and avoiding contact with infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…An outbreak in a hematologic/ oncologic unit resulted in 23/76 patients (32%) developing nosocomial influenza, three patients being identified with oseltamivir-resistant virus, and 3 patients expiring (27). An outbreak investigation in the Netherlands found nosocomial transmission of oseltamivir-resistant virus, leading to three cases of pneumonia and two mortalities (28).…”
mentioning
confidence: 99%
“…6) Moreover, recent studies have indicated that pandemic H1N1 Tamiflu-resistant (H1N1 TR) viral isolates have been progressively rising, which may pose a risk for increasing fatality in human beings. 7,8) This means that development of new therapeutic agents are urgently needed and prompted us to synthesize some novel flavonoids and explore the possibility as potential anti-influenza agents.…”
mentioning
confidence: 99%